Genetic diversity and demographic history of the dromedary camel (Camelus dromedarius) - Almathen, Faisal (2014)
The dromedary camel (Camelus dromedarius) commonly referred to as ‘ship of the desert’ has played an important part in the development and expansion of trading networks across inhospitable habitats over 3000 years, linking Arabian, Asian, African and European civilisations. Caravan roads, which are part of the major trading networks, have facilitated livestock exchange across large geographic distances. Dromedary camels are known to have been extensively used as pack animals along these caravan roads. Archaeological records point towards the southern Arabian Peninsula as the origin of the domestic dromedary camels. However, there is uncertainty about the dromedary’s dispersal out of the Arabian Peninsula to Africa and other parts of Asia. In contrast to other livestock species, the domestication of the dromedary camel has not been investigated using genetic evidence. Also, there is no information available on the genetic relationship between dromedary populations across their entire geographic distribution. Previous genetic studies were limited to a restricted number of animals, often from a single population or a small geographic region within countries. The general aims of this thesis were to characterise the origin and the geographic distribution of genetic diversity in dromedary camels and to understand the demographic history across the species range. To ascertain the global genetic structure and to contribute to the knowledge on the spread of the species after domestication, we sampled 1,083 modern-day dromedary camels from 21 countries representing the species range. Mitochondrial DNA and microsatellite markers were used for these analyses. Nine hundred and seventy animals were investigated using 17 autosomal microsatellite loci, and 759 animals were studied at the mitochondrial DNA level using a continuous 867 bp fragment spanning the end of cytochrome b, the tRNAs threonine and proline, and the beginning of the control region.